Survival of patients with transformed follicular lymphoma in the United States: a multiple cohort study - John L. Vaughn; Narendranath Epperla (BMC, 2023)
Abstract Population-based data comparing the outcomes of patients with transformed follicular lymphoma (t-FL) and de novo diffuse large B-cell lymphoma (DLBCL) are lacking. The objective of this study was to compare the survival of patients with t-FL and de novo DLBCL diagnosed in the United States between 2010-2018. We hypothesized that patients with t-FL would have an inferior survival compared to patients with de novo DLBCL. The study outcomes were relative survival (RS), overall survival (OS), and lymphoma-specific survival (LSS) compared between t-FL and de novo DLBCL. Flexible parametric survival models were used to estimate the study outcomes. There were 569 cases of t-FL and 44,706 cases of de novo DLBCL. Patients with t-FL had an estimated 5-year RS of 54% [95% confidence interval (CI), 49-59%) compared to 67% (95% CI, 66-67%) for those with de novo DLBCL (adjusted hazard ratio, 1.29; 95% CI, 1.11-1.50; P = 0.001). The corresponding 5-year OS estimates were 49% (95% CI, 44-53%) and 57% (95% CI, 57-58%), respectively (adjusted hazard ratio, 1.23; 95% CI, 1.07-1.42; P = 0.004). The corresponding 5-year LSS estimates were 54% (95% CI, 50-59%) and 66% (95% CI, 65-66%), respectively (adjusted hazard ratio, 1.34; 95% CI, 1.15-1.56; P < 0.001). This population-based registry analysis shows that patients with t-FL continue to have an inferior survival in the modern era and should be prioritized for enrollment in clinical trials.